Genetic skeletal disorders: phenotypic-genotypic characteristics and RhGH therapy responses of a pediatric cohort - Yiyun Huang; Yan Peng; Chuan Li; Bobo Xie; Xianda Wei; Baoheng Gui; Juan Meng; Shaoke Chen; Xin Fan (Scientific Reports)
Abstract This study aimed to explore the genotype-phenotype correlations in individuals with Genetic Skeletal Disorders (GSD), evaluate the efficacy of recombinant human Growth Hormone (rhGH) therapy. The retrospective analysis of the medical records of 80 pediatric patients with GSD diagnosed via whole-exome sequencing was conducted. The therapeutic effects of rhGH treatment were analyzed in 30 of these patients who received rhGH therapy. The study included 80 GSD patients, diagnosed at a median age of 4.88 years, with a median height standard deviation score (Ht-SDS) of − 3.58. The most common clinical manifestations included skeletal deformities (87.5%), short stature (81.3%), and distinctive facial features (including triangular face, abnormality of the philtrum, abnormality of the forehead, etc.) (65.0%). A total of 33 pathogenic genes associated with 20 groups of GSD were identified. The most common groups are Type II collagenopathies (related to the COL2A1 gene) (12/80, 15.0%) and the FGFR3-related chondrodysplasia group (12/80, 15.0%). Those with pathogenic genes linked to Fundamental Cellular Processes had more severe short stature and prenatal phenotypes. Thirty patients received rhGH treatment for a median of 2.25 years (0.33–8.92), showing Ht-SDS increases of 0.66 ± 0.42 and 0.84 ± 0.52, after one and two years, respectively (p < 0.001). Eight untreated patients had an average Ht-SDS decrease of − 0.46 ± 0.55. In this cohort, pediatric GSD patients predominantly presented with short stature, skeletal deformities, and distinctive facial features (including triangular face, abnormality of the philtrum, abnormality of the forehead, etc.), indicating a genotype-phenotype correlation. Compared to untreated GSD patients, those receiving rhGH treatment demonstrated varying degrees of height improvement, however, the long-term efficacy of this treatment warrants further investigation.